Legal Analysis of Investor Protection in Corporate Green Bond Issuance - Pakpahan, Elvira Fitriyani; Heriyanti, Heriyanti; Tanjaya, Willy; Pakpahan, Emir Syarif Fatahillah; Rizal, Said; Leonard, Tommy (UI Scholars Hub, 2024)
The global climate crisis has driven countries, including Indonesia, to adopt sustainable financing mechanisms that channel capital into environmentally responsible projects. One prominent instrument is the green bond—debt securities issued by corporations or institutions to finance projects with measurable environmental benefits, such as renewable energy, sustainable transport, and climate change mitigation. In Indonesia, green bonds are regulated by the Financial Services Authority (OJK) through Regulation No. 60/POJK.04/2017, which sets administrative requirements for issuance. While this framework marks an important step, it remains inadequate to guarantee strong investor protection. Current provisions do not establish clear enforcement mechanisms or effective sanctions against fund misallocation or project deviation, leaving investors vulnerable to risks such as greenwashing. The absence of mandatory third-party verification and the lack of supporting jurisprudence further undermine transparency, accountability, and the legal standing of investors. This research analyzes the extent of legal protection for investors in Indonesian corporate green bond issuances and evaluates the adequacy of existing regulations. It also proposes reforms—such as mandatory independent verification, explicit liability provisions, and the integration of national standards—to enhance safeguards for investors and strengthen market credibility. In the context of global momentum toward ESG-based investment and Indonesia’s commitments under the Paris Agreement and the Sustainable Development Goals (SDGs), establishing a more comprehensive and enforceable legal framework is essential. Such a framework would not only ensure genuine environmental impact but also build investor confidence in Indonesia’s growing green finance market.